Videos of Basal Ice in Boreholes on the Kamb Ice Stream in West Antarctica - Engelhardt, Hermann (IEDA: US Antarctic Program Data Center, 2013)
This data set is a collection of video data of basal ice taken in a borehole on the Kamb Ice Stream in West Antarctica. Ice streams are an expression of the inherent instability of the West Antarctic Ice Sheet, and their behavior is a key control on the overall ice-sheet mass balance. Understanding the response of the ice sheet in a warming climate requires a thorough understanding of the internal dynamics of ice streams, in addition to the relevant ice-atmosphere and ice-ocean interactions in the region. The basal environment of the ice streams and of many glaciers is a key scientific interest, including conditions, mainly basal sliding, that lead to fast flow of the ice. The purpose of this data set is to present a review of the full range of original video recordings from the basal ice of the Kamb Ice Stream. Direct observations at the ice-stream bed are a crucial complement to modeling efforts predicting future scenarios in a warming climate.